AS ATIVIDADES DE EXTENSÃO COMO COMPROMISSO SOCIAL: UM ESTUDO DE CASO NO INSTITUTO FEDERAL DE SANTA CATARINA (IFSC) E NA FUNDAÇÃO UNIVERSIDADE DO ESTADO DE SANTA CATARINA (UDESC) - Raquel Matys Cardenuto (Universidade Federal de Santa Catarina, 2017)
This article aims to understand the importance of extension activities in Higher Education Institutions (HEIs), carried out in an articulated way between research and teaching, promoting interdisciplinarity, as one of the means to achieve social commitment. It is a case study where, through a bibliographic and documentary research at the Federal Institute of Santa Catarina (IFSC) and at the State University of Santa Catarina Foundation (UDESC), the actions and projects developed during the 2012 to 2015 were identified. After analyzing the data, it was verified that the two institutions have well-defined policies, being committed to university extension, encouraging the development of their projects and actions through notices, with allocation of own resources and fundraising external. It was observed that the strengthening of the extensionist culture is one of the major challenges of HEI managers, and the sensitization and integration of the academic community becomes fundamental so that the extension can serve its purposes as a transforming link between the university and society.